The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.26508/lsa.201900517
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of colorectal cancer subtypes and cell lines using deep learning

Abstract: A deep learning approach refines the state-of-the-art subtypes of colorectal cancer and evaluates the fidelity of cell lines that model cancer.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 55 publications
(73 reference statements)
0
77
0
Order By: Relevance
“…Cell lines are commonly used as models for tumors; however, it is an open question how to best apply the available cell line panels to learn about cancer biology. The availability of genomic data from large tumor cohorts and from cell line panels has spurred efforts to find which cell lines are closer to tumors by their transcriptomic (9,37,38) and/or genomic features (12,13), presumably making better models, and which are more distant from examples of actual tumors, thus making less good models.…”
Section: Discussionmentioning
confidence: 99%
“…Cell lines are commonly used as models for tumors; however, it is an open question how to best apply the available cell line panels to learn about cancer biology. The availability of genomic data from large tumor cohorts and from cell line panels has spurred efforts to find which cell lines are closer to tumors by their transcriptomic (9,37,38) and/or genomic features (12,13), presumably making better models, and which are more distant from examples of actual tumors, thus making less good models.…”
Section: Discussionmentioning
confidence: 99%
“…observed that OC316 was hyper-mutated 12 , Sinha et al found that SLR20 had an outlier copy number profile 57 , and Ronen et al found that COLO320 was dissimilar to colorectal tumors and lacked major colorectal cancer driver genes 58 . In our analysis, all of these cell lines were also identified as being unlike their respective tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…For breast cancer, cell lines subtypes have been assigned mainly using Prediction Analysis for Microarrays (PAM) analysis, which is based on a restricted set of gene expression markers (38). For colorectal cancer, the cell lines were stratified into the consensus molecular subtypes (CMS) integrating transcriptomic and genomic data (39). For renal cancer, subtypes were assigned to the cell lines using gene expression data (14).…”
Section: Resultsmentioning
confidence: 99%
“…Cell lines are commonly used as models for tumors, however it is an open question how to best apply the available cell line panels to learn about cancer biology. The availability of genomic data from large tumor cohorts and from cell line panels has spurred multiple efforts to find which cell line(s) are closer to tumors by their transcriptomic (10,39,40,46) and/or genomic features (13,14), presumably making better models, and which are more distant from examples of actual tumors, presumably making less good models of tumor biology.…”
Section: Discussionmentioning
confidence: 99%